Mei’s symmetry theorem for time scales nonshifted mechanical systems - Yi Zhang (Elsevier, 2021)
We focus on Mei symmetry for time scales nonshifted mechanical systems within Lagrangian framework and its resulting new conserved quantities. Firstly, the dynamic equations of time scales nonshifted holonomic systems and time scales nonshifted nonholonomic systems are derived from the generalized Hamilton’s principle. Secondly, the definitions of Mei symmetry on time scales are given and its criterions are deduced. Finally, Mei’s symmetry theorems for time scales nonshifted holonomic conservative systems, time scales nonshifted holonomic nonconservative systems and time scales nonshifted nonholonomic systems are established and proved, and new conserved quantities of above systems are obtained. Results are illustrated with two examples.